Neutral monosaccharides and their relationship to metal contamination in mangrove sediments. (July 2020) - Duan, Dandan; Lan, Wenlu; Chen, Fengyuan; Lei, Pei; Zhang, Hao; Ma, Jie; Wei, Yang; Pan, Ke
Abstract: Mangrove sediments act as an important natural sink and a secondary source for trace metals. The main objective of this study was to investigate metal contamination and its relationship to mangrove-derived carbohydrates in mangrove sediments. Sixteen metals (Be, V, Cr, Co, Ni, Cu, Zn, Ga, As, Sr, Cd, Sn, Sb, Ba, Tl, and Pb）were analyzed in the surface sediments from four sites at different latitudes on the southeast coastline of China. The sedimentary organic matter was characterized by Rock-Eval pyrolysis, and the neutral sugars were examined by gas chromatograph mass spectrometry. Our results from the enrichment factors indicated that the mangrove sediments were no enriched by Ga, Sr, and Ba, minor enriched by Be, V, Cr, Co, Ni, Cu, Zn, As, Sn, Sb, Tl, and Pb, and moderate enriched by Cd. Litterfall was a major source of organic matter in the mangrove sediments, and the neutral sugars were mainly derived from this litterfall. Significant correlations were detected between the total organic carbon, pyrolytic parameters, neutral sugars, and enrichment factors of V, Cr, Co, Ni, Zn, and Cd, suggesting the input of neutral carbohydrates played an important role in enhancing the metal accumulation in the mangrove sediments. The mangrove litterfall itself was a major source of metals for the sediments, and the mangrove-derived organic matter enhanced the sediment's metal accumulation. Highlights: Metal concentrations in mangrove sediments decreased from low to high latitudes. Litterfall was the main source of organic matter in the mangrove sediments. V, Cr, Co, Ni, Zn, Cd were strongly correlated with mangrove-derived carbohydrates. Litterfall was both a metal source and metal storage pool in the sediments.